Superficial Temporal Artery Pseudoaneurysm: A Case Report - Younus, Syed Muneeb; Imran, Muhammad; Qazi, Rabia (Frontiers in Surgery, 2015)
Pseudoaneurysms of the superficial temporal artery are an uncommon vascular lesion of the external carotid system and most often the result of blunt head trauma. The frequency of pseudoaneurysms of the superficial temporal artery developing after craniotomy is exceedingly low and only a few cases have been reported. We present a case of pseudoaneurysm of this type in a 45-year-old male who underwent craniotomy for excision of meningioma. One month postoperatively, the craniotomy flap exhibited an enormous diffuse pulsate swelling. The suspected diagnosis of pseudoaneurysm arising from superficial temporal artery was confirmed on angiography. Surgical excision was done and no recurrences of the tumor or aneurysm were noted on subsequent follow up.